Drilling Waste Management Strategy for Field ‘X’ - Risyad Ramadhan Wibowo; Sugiatmo Kasmungin; Agung Budi Rudiantoro (Lembaga Penelitian Universitas Trisakti, 2015)
Drilling waste management is a planing and implementation of a prudent drilling waste collection,treatment and final disposal. A well planned drilling waste management system not only ensure thehealth and safety of the surrounding environment, it also brings advantages to the drilling operationeffectivity and economics. The drilling waste management technologies and practices can begrouped into three major categories : waste minimization, recylce/reuse and disposal. This essaywill later discuss about planning a fit for purpose drilling waste management system for a new fieldby studying the waste generation from previous drilling activity, estimating waste generation of theplanned wells, creating and evaluating drilling waste management scenarios and choosing the bestscenario based on its environment safety, cost and doability through SWOT and analytic hierarchyprocess.